Temperature Changes During Cryoeffect Potentiated With Distilled Water Assessed in Porcine Liver Model Without Splanchnic Blood Flow - Dronov, Oleksiy I.; Khomenko, Dmytro I.; Bakunets, Petro P.; Teteryna, Viktoria V. (Problems of Cryobiology and Cryomedicine, 2017)
The efficiency of local cryoeffect on pathological tissue area depends on the values of achieved temperature at a certain depth. This study presents the results on comparative analysis of the dynamics of temperature changes measured by intraoperative four-channel thermocouple unit KVIT-4 at discrete depths of 3, 8, 13 and 18 mm. We carried out two successive cycles of local cryoeffect with preliminary introduction of a distilled water into parenchyma of porcine liver (main group) and without any additional action (control group) in experimental model of porcine liver without splanchnic blood flow. The average temperature in animal liver tissue of the main group at a distance of 3 mm deep from the cryoapplicator operating surface was lower by 35 degrees at the end of the 10th min of cryoeffect of the 2nd cycle if compared with the control (–85.2 and –49.2°C, respectively), at a depth of 8 mm it was lower by 52,5 degrees (–61.1 and –8.5°C, respectively), at 13 mm this index was lower by 51,5 degrees (–59.5 and –3.0°C, respectively), and at 18 mm it was lower by 40,4 degrees (–40.5 and –0.1°C, respectively). An introduction of a distilled water into biological tissue 5 min prior to the initiation of local cryoeffect increased its effectiveness, as evidenced by the reaching of lower temperatures in the areas distant from the operating surface of the cryoapplicator. Probl Cryobiol Cryomed 2017; 27(4): 348–355